Spontaneous Epidural Hematoma: A rare neurological complication in a patient following routine coronary angiography - Shakya, Smriti; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Manandhar, Bhawani; Khanal, Rajaram; Yadav, Sutap; KC, Ashmita (Nepalese Heart Journal, 2023)
Spinal epidural hematoma is an uncommon but potentially devastating complication associated with various medical interventions. We present a case report of this rare neurological complication following a routine coronary angiography. A 69-year-old male with Aortic Stenosis presented for a scheduled coronary angiography to assess his cardiac status before valve replacement. The procedure was uneventful but approximately 15 minutes after the angiography, he developed sudden-onset of rapidly progressing weakness and numbness in bilateral lower extremities. An urgent neurologic evaluation revealed signs of spinal cord compression, prompting a magnetic resonance imaging (MRI) scan which showed an extensive spinal epidural hematoma spanning multiple levels within the cervicothoracic spine. This case highlights the importance of recognizing this rare but a potential complication following routine coronary angiography even in the absence of signifcant procedural complications. Timely diagnosis and prompt surgical intervention are crucial for achieving favorable outcomes and minimizing morbidity associated with this condition.